Polymer artificial stone with electric energy storage function and manufacturing method thereof

A high-energy density and voltage artificial stone supercapacitor was developed by using geological polymer/cement composites and MXene/Ag nanoparticles-coated steel electrodes, solving the energy density and voltage limits of existing capacitors and batteries , realizes environmentally friendly and cost-effective power storage.

CN119452445APending Publication Date: 2025-02-14KAYHAN SWISS GMBH

Patent Information

Application Number
CN202380049280.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-05-05
Filing Date
2023-05-04
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

In the prior art, the energy density and voltage of capacitors and batteries limit their wide application in buildings, and traditional battery materials are not environmentally friendly.

Method used

A new type of artificial stone supercapacitor was formed by using geological polymer/cement composites as the electrolyte matrix and steel electrodes coated with MXene and Ag nanoparticles.

Benefits of technology

It realizes high energy density and voltage electrical energy storage, reduces production costs, and is environmentally friendly in materials, suitable for building facade electrical energy storage.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119452445A_ABST
    Figure CN119452445A_ABST
Patent Text Reader

Abstract

The artificial stone can be used as an electric energy storage device which is similar to a super capacitor, and the preparation method of the artificial stone is disclosed. According to the invention, geopolymers and cement are used as materials for electrolytes. The supercapacitor of the invention comprises a geopolymer and cement matrix (1) and positive and negative steel electrodes (2, 3), whereby the steel electrodes (2, 3) are arranged in the matrix, which is prepared from an electrically conductive mortar. Conductive mortars include fly ash, cement, gravel and sand, alkaline activators (KOH and SiO2), and additives to some artificial stone compounds, such as polycarboxylic acid ethers, retarders, lignosulphonate, ethylene-vinyl acetate, hydroxypropyl methyl cellulose, pigments, MXene and carbon black. The super capacitor artificial stone is simple in structure and is based on a specific formula.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to artificial stone as an electrical energy storage. The present invention also discloses a method for manufacturing and using such artificial stone as an electrical energy storage. Therefore, the present invention relates to a method capable of manufacturing artificial stone and using it as a capacitor and battery, so that in the method the new artificial stone combination comprises a geopolymer / cement composite material (i.e. a geopolymer cement-based composite material) as an electrolyte in the form of a mortar matrix, which can be used as an electrolyte matrix, and two pieces of steel as electrodes. The method is both practical and cost-effective. Background Art

[0002] In the future, structural materials will take on additional functions, such as collecting and storing electricity from solar and wind renewable energy sources. This function will not only improve the energy efficiency of buildings, but also enable better management of excess energy by feeding it to the grid to reduce peak energy demand or using it to power auxiliary systems such as lamp posts, traffic lights, billboards, electric vehicle charging stations and structural health monitoring sensors. In order to reduce fuel costs and reduce environmental pollution, it is necessary to develop a new type of battery.

[0003] Capacitors offer high power density but limited energy density. Concrete is the most used material in the world after water. Researchers have been exploring the idea of ​​using concrete to store electricity, essentially building buildings that act as giant batteries. Cement is a dielectric material that contains water. In cement, the water is present inside and outside of silicate hydrate crystals. Electrolytes are ionic dielectric materials that conduct electricity through the movement of ions. In other words, electrolytes are electronic insulators but are ionic conductors. Batteries consist of a negative electrode, which is an electrode that acts as an electronic conductor and undergoes chemical oxidation during battery discharge, and a positive electrode, which is an electrode that acts as an electronic conductor and undergoes chemical reduction during battery discharge. The two electrodes are separated by an electrolyte. During discharge, a voltage appears between the positive and negative electrodes.

[0004] In general, this idea is gaining popularity as many places become more and more dependent on renewable energy sources from wind and solar. When the wind dies down or night falls, rechargeable batteries are indispensable, but so far they are usually made of toxic substances that are very environmentally unfriendly. For this reason, it is recommended to use environmentally friendly materials instead.

[0005] Experimental concrete batteries have only managed to retain a fraction of the capacity of conventional batteries. For this reason, efforts to increase the capacity of batteries and supercapacitors are the subject of discussion among many researchers. Research on electrical energy storage in civil engineering structures remains scarce, and only a few concepts for cement-based structural electrical energy storage systems have been proposed so far. These cement-based energy storage systems use pore solutions in cement as electrolytes and cement with additives such as graphene, black carbon, zinc, magnesium dioxide, etc. as electrodes. The concept of cement-based batteries can be extended from cement to concrete by adding aggregates. Concrete refers to cement filled with aggregates. Although aggregates do not participate in the electrochemical reaction, they are often used in cement-based structures for the purposes of mechanical reinforcement, reduced drying shrinkage, and reduced cost. The presence of aggregates in cement-based electrolytes is expected to lead to an increase in the thickness of the electrolyte layer. An increase in thickness is undesirable because it will result in a higher resistance of the electrolyte layer in the direction perpendicular to the layer, and this resistance will increase the overall battery resistance.

[0006] Residential and commercial buildings consume nearly 40% of the total energy consumption of society for heating and / or cooling, and zero-energy buildings are increasingly attracting the attention of researchers. In the future, advanced structural materials used on a large scale are expected to provide new smart functions, such as building materials for energy storage and electricity storage to reduce the pollution of chemical batteries. The use of cheap and abundant materials (such as cement and geopolymers) in batteries and supercapacitors makes the development of large-scale storage possible. Geopolymers are a new cement-free binding material that has been widely studied to replace Portland cement. Geopolymers are made by reacting materials rich in silica and alumina with alkaline solutions. The preferred raw materials are fly ash, slag and metakaolin, and the most commonly used alkaline activators are sodium hydroxide and sodium silicate. These solutions react with active silica (SiO2) and alumina (Al2O3) to form a Si-O-Al network. Burstein et al. have disclosed cement-based batteries and supercapacitors using cement-based electrolytes. In such supercapacitors, two electrodes are immersed in an electrolyte, and the two electrodes are separated by an ion-permeable membrane, which is an electronic insulator that prevents electrical contact.

[0007] U.S. Patent Application 2021 / 0119249A1 published on April 22, 2021 describes a voltage source that operates, for example, as a secondary battery (i.e., functionalized to have an electrical or energy storage function), comprising an electrolyte formed using an alkaline activator (e.g., sodium hydroxide (NaOH), potassium hydroxide (KOH), sodium sulfate (Na2SO4), sodium carbonate (Na2CO3), potassium sulfate (K2SO4), potassium carbonate (K2CO3)), the electrolyte comprising, for example, a cement binder composition, and having a mixture of main components including aluminum and silicon oxide; the electrolyte also comprises fly ash, sand, gravel, and additives. The two electrodes are made of aluminum, chalky carbon, and steel.

[0008] Patent publication CN113436899A discloses a geopolymer-based supercapacitor, which includes a geopolymer matrix, a metal electrode and a capacitor wire. The conductive slurry contains potassium silicate aqueous solution, ferrosilicon powder, chlorinated fly ash, lithium and sodium fluoride. The modified solution consists of a NaOH solution and a NaHCO3 solution.

[0009] Patent publication CN113666654A discloses a conductive slurry based on building materials for forming a supercapacitor, the slurry having modified fly ash, a modified alkaline activator and an ion enhancer. The modified solution composed of NaOH solution and NaHCO3 solution can destroy part of the glassy structure and protective film on the surface of the fly ash, so that the structure of the modified fly ash becomes looser and more porous than that of ordinary fly ash. Lithium chloride, sodium fluoride, ferrosilicon powder and potassium silicate aqueous solution are added to the geopolymer, and the released lithium ions and fluoride ions, due to their small size, can pass through the silicon aluminum oxide (-Si-O-Al-O-) tetrahedron formed in the hardened geopolymer and move in a directional manner, thereby improving the conductivity of the geopolymer. Patent publication CN113436907A describes a geopolymer-based supercapacitor, which includes a matrix prepared by a conductive slurry; the conductive slurry contains modified fly ash, a modified alkaline activator and an ion enhancer. The geopolymer matrix is ​​made of conductive slurry, which contains modified fly ash, modified alkaline activator and ion enhancer. The modified fly ash is made of ordinary fly ash, NaOH and NaHCO3, the modified alkaline activator is made of ferrosilicon powder and potassium silicate aqueous solution, and the ion enhancer is made of lithium chloride and sodium fluoride. The geopolymer matrix contains a preset number of free ions that can move in a directional manner to generate current. The positive and negative metals are copper sheets or copper alloy sheets.

[0010] Conductive fillers such as porous activated carbon (AC), graphene, carbon nanotubes (CNT), carbon fibers, and other carbon-based materials are commonly used in commercial supercapacitor manufacturing to improve conductivity. However, low volumetric performance, including low energy density (<20 mWh / cm 3 ), low volume capacitance (<200F / cm 3) and lower operating voltage (<2.7V)) are the main challenges in current supercapacitor research. Therefore, advanced electrode materials with higher capacity, higher voltage and energy density are urgent and desirable for future supercapacitors. Relying on its unique structure, large surface area, high electrical and thermal conductivity, fast ion diffusion, thickness and composition controllability, MXene's incredible related structure with layered morphology, fast electron transport and fast ion diffusion capabilities, inherent high electronic conductivity (up to about 24000S / cm), hydrophilicity, favorable pseudocapacitive properties and rich surface functionality play an important role in high electrochemical energy storage performance, surpassing other 2D materials.

[0011] The effect of MXene on cement properties shows that MXene inhibits the early hydration of cement. At the same time, with the addition of MXene, the total hydration heat of cement hydration increases. It can be concluded that the use of a small amount of MXese in conductive mortar can effectively improve the compressive strength of the mortar. The addition of MXene can also reduce the resistivity. This conductive additive connects with each other in cement-based materials, forming a good conductive path and conducting electricity.

[0012] Electrode materials with high conductivity are important components of supercapacitors. In recent years, 2D electrode materials have been widely studied due to their high specific surface area, excellent electronic and mechanical properties, especially MXenes, a new family of 2D materials with metallic conductivity and hydrophilic surface.

[0013] The development of MXene-based electrodes has achieved remarkable progress in electrical performance and has been used in supercapacitors, as demonstrated by combining such electrodes with PVA-H2SO4 polymer as the electrolyte.

[0014] The self-restacking of MXene nanosheets leads to an increase in the “dead” area, resulting in a fatal loss of available surface area, preventing the electrolyte from penetrating into the layers, and limiting the electrochemical performance and practical applications of electrode materials. The introduction of interlayer spacers between sheets is an effective strategy to prevent heavy stacking while increasing the specific surface area. The electrochemical performance can also be improved by increasing the electrode / electrolyte interface area and reducing the ion diffusion length within the active material.

[0015] MXene-metal nanocomposites have shown promising performance as electrochemical capacitor electrode materials using metal nanoparticles (NPs) as spacers. In particular, silver (Ag) nanoparticles have the highest conductivity among noble metals and exhibit a large surface area to volume ratio at the nanoscale level, making them excellent nanomaterials for energy storage devices that require a large surface area. Current work suggests that combining other materials with MXenes to prepare MXenes-based composite electrode materials is one of the most effective strategies for energy storage applications.

[0016] There is a need to develop a geopolymer based supercapacitor in the form of an artificial stone. The present invention provides a supercapacitor stone comprising a new conductive filler in the mortar and an active material on the metal electrodes. There are currently no supercapacitors made of artificial stone with such electrodes and there is a need for development of electrical storage in the civil engineering field. Summary of the invention

[0017] Purpose of the invention

[0018] The purpose of the present invention is to eventually change the structure of similar capacitors and batteries and approach stone structures for applications in buildings. Another purpose of the present invention is to improve the efficiency and life of the battery. In view of the information given above, the technical problem to be solved by the present invention is to provide an artificial stone supercapacitor that no longer requires a chemical supercapacitor and can be used for the architectural facade of a building; another purpose of the present invention is to provide a manufacturing method for manufacturing the artificial stone supercapacitor, which is simple, low-cost and easy to prepare and implement.

[0019] Technical solution of the present invention

[0020] The technical problem is solved by an artificial stone comprising a geopolymer-cement matrix and two steel electrodes immersed in an electrolyte matrix of the geopolymer-cement matrix, thereby providing electrical energy storage functionality. The geopolymer-based battery is superior in performance to cement-based batteries.

[0021] The manufacture of the artificial stone includes the following steps:

[0022] A) preparing a conductive mortar as a slurry,

[0023] B) Preparation of steel electrodes coated with MXene and Ag mixture,

[0024] C) Place two steel electrodes into the mold,

[0025] D) Pour the conductive paste into the mold,

[0026] E) curing the conductive slurry for 48 hours to obtain a solid artificial stone supercapacitor. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to make the objectives, technical solutions and advantages of the present invention more clear, the present invention will be further described in detail below with reference to the accompanying drawings.

[0028] Displayed is:

[0029] Figure 1 : Typical process for alkaline batteries;

[0030] Figure 2 : The structural representation of the artificial stone of the present invention. DETAILED DESCRIPTION

[0031] Technical theory of cement-based composite batteries

[0032] Traditional batteries consist of a negative electrode, a positive electrode, and an electrolyte, such as Figure 1 In any battery, ions and electrons move from the negative electrode to the positive electrode through an electrolyte and a circuit, respectively. A typical alkaline battery uses zinc as the negative electrode, manganese dioxide as the positive electrode, and a salt solution as the electrolyte. The electrolyte should have high ionic conductivity and low resistance, allowing it to carry high currents. Liquid electrolytes generally perform better due to the high mobility of ions.

[0033] Cement-based composite batteries are suitable for these general battery concepts, such as Figure 2 As shown. Burstein and Speckert and Sakai et al. have disclosed cement-based batteries using cement-based electrolytes. Using cheap and abundant materials (such as cement) for batteries makes it possible to develop large-scale batteries. In addition, by incorporating cement-based batteries as part of a building, the battery does not consume additional energy and can provide a large amount of energy. In other words, the battery becomes integrated with the building.

[0034] Geopolymer Batteries and Supercapacitors

[0035] There is currently an increasing interest in integrated monitoring and maintenance technologies, particularly through the application of "smart cements". These cements can act as repair materials for concrete structures while undergoing measurable changes in electronic impedance in response to environmental conditions. Geopolymers are synthesized by mixing solid waste (reactive materials rich in aluminosilicates, such as ground granulated blast furnace slag (GGBFS), fly ash) with an alkaline activator (a strong alkaline solution, such as NaOH or KOH) and then curing at room temperature or elevated temperature. Geopolymers have the following advantages over cement: (a) low fuel consumption and carbon dioxide emissions during manufacturing; (b) better mechanical properties; (c) rapid hardening; and (d) better fire resistance and acid attack resistance. Geopolymers show good prospects in the field of energy storage because of their high durability, multiple physical properties, and tolerance to extreme environmental conditions. For many years, geopolymers have been developed as protective coating materials for marine concrete and transportation infrastructure. However, one challenge in the application of geopolymers in this field is that they are usually cured at high temperatures above 40°C. In the present invention, the geopolymer cementitious composite material used therein is formed by alkaline activation of aluminosilicate materials. Fly ash mortar was used as the source of geopolymer.

[0036] According to the present invention, the geopolymer-cement matrix is ​​made of a conductive mortar, which includes fly ash, cement, gravel and sand, alkaline activators (KOH and SiO2), and some additives of artificial stone compounds (for example, one or more of polycarboxylate ethers, retarders, lignin sulfonates, ethylene-vinyl acetate, hydroxypropyl methylcellulose and pigments). Carbon black and MXene can be added to the mortar to improve and increase output, especially current and life.

[0037] The mortar and the matrix utilize the pore solutions in cement and geopolymers, which contain a predetermined number of freely mobile ions that can store energy.

[0038] In the present invention, MXene is used as an electrode coating and electrolyte additive. MXenes is a new type of two-dimensional ceramic material, which has a formula M n+1 X n T x MXene is composed of n+1 (n=1-3) layers of pre-transition metal (M) and n layers of carbon or nitrogen (X), with the general formula M n+1 X n T x , where M refers to a transition metal (such as Sc, Ti, Zr, V, Nb, Cr or Mo); X refers to a C or N element, T x = represents the surface end groups (-OH, =O, and / or -F). These excellent surface groups themselves can provide a large number of active sites, which have great potential for surface modification and effective loading of active materials. MXenes have good electrical and thermal conductivity, high strength, light weight, good thermal stability and easy processing. MXenes can be compounds Ti3C2T x 、Ti2CT x 、Ti3CNT x 、TiNbCT x 、Ta4C3T x 、Mo2CT x 、Mo2TiC2T x 、Mo2Ti2C3T x 、Nb4C3T x 、Nb2CT x ,(V 0.5 Cr 0.5 )3C2T x 、V2CT x 、Zr3C2T x 、Hf3C2T x One of the above.

[0039] The preparation work for manufacturing the artificial stone includes the following steps:

[0040] A) preparing conductive mortar,

[0041] B) Preparation of steel electrodes coated with MXene and Ag mixture,

[0042] C) Place two steel electrodes into the mold,

[0043] D) Pour the conductive paste into the mold,

[0044] E) Curing for 48 hours to obtain a solid artificial stone supercapacitor.

[0045] The preparation of the conductive mortar can be carried out according to the detailed example given below, by:

[0046] A1) preparing an alkaline activator consisting of a potassium silicate (K2SiO3) solution containing SiO2=7.98 g, KOH=9.21 g, and H2O=15 g;

[0047] A2) preparing an additive solution comprising polycarboxylate ether = 0.25 g, retarder = 0.01 g, lignin sulfonate = 0.2 g, ethylene vinyl acetate = 0.2 g, hydroxypropyl methylcellulose = 0.1 g and pigment = 0.5 g; stirring all additives in 5 g of deionized water for 30 minutes;

[0048] A3) sonicating 1.44 g of carbon black in water using a probe;

[0049] A4) ultrasonically dispersing 0.08 g of MXene in 5 g of water for 5 minutes;

[0050] A5) The obtained solution was added into 20 g of fly ash, 25 g of cement and 5 g of gravel and sand, and then stirred evenly and then allowed to stand to obtain a mixed solution.

[0051] The preparation method of the steel electrode coated with MXene can be carried out by the detailed example given below, through:

[0052] B1) MXene (d-Ti3C2T x ) suspension.

[0053] B2) 0.5 g of Ti3AlC2 was slowly added into the mixture over a period of about 5 minutes, and the mixture was reacted at 35°C with stirring for 24 hours.

[0054] B3) The MXene suspension was sonicated using a tip sonicator for 1 hour.

[0055] B4) The MXene suspension was then centrifuged at 3500 rpm for 30 minutes, and the supernatant was collected and used as the MXene suspension.

[0056] B5) Ag NPs (0.03 mg / mL) were added to the MXene suspension under vigorous stirring, and the solution was stirred for another 30 min.

[0057] B6) Steel was cut into dimensions of 70 mm x 60 mm x 20 mm. The resulting suspension was sprayed 7 times on a cut mesh having a polyethylene terephthalate film prebaked on a hot plate at 50°C.

[0058] Advantageously, if Figure 2 As shown, the steel electrodes 2, 3 are placed in the rectangular mold 1, and the distance between the positive electrode 2 and the negative electrode 3 is maintained within the range of 8 mm.

[0059] The implementation of the present invention has the following beneficial effects: the matrix in the artificial stone supercapacitor of the present invention contains many free ions. The pores in the mortar of the artificial stone transmit ions to the electrodes and are a factor in energy storage. Therefore, the matrix can be a solid electrolyte, which can prevent electrical contact. These artificial stones can be connected to an external power source to complete charging, and then connected to an electrical appliance to complete discharging. It can be used for building facades, thereby realizing the electrical energy storage function of building materials and saving a lot of energy.

[0060] According to the invention, a geopolymer cementitious composite material is used, which is formed by alkaline activation of aluminosilicate materials (e.g. fly ash). In the chemical process of the invention, the alkaline activator consists of a mixture of silicate (SiO2) and potassium hydroxide (KOH). Depending on the Si / Al molar ratio, after reaction at controlled temperature, the resulting geopolymer framework can be in the form of potassium-poly(sialate-siloxo) (KPSS) to produce ionic conductivity in the mortar.

[0061] According to the invention, the artificial stone matrix contains the new material MXene, which is able to give the stone good electrical properties and compressive strength.

[0062] According to the invention, the steel electrode in the supercapacitor contains a MXene layer (Ti3C2T x ), which shows great potential in electrical energy storage.

[0063] Artificial stone supercapacitors offer a practical and cost-effective way to store energy. They offer a green and environmentally friendly way to store energy and they can be used in building facades to make buildings more multifunctional. In addition, the supercapacitors allow building structures to deliver electricity on demand, so that this demand does not always have to rely entirely on electricity delivered from a long distance. Intermediate storage is provided, which can be charged in case of overproduction of electrical energy and from which electrical energy can be drawn in case of shortage.

[0064] The artificial stone supercapacitor of the present invention as described above does provide a capacity of 35mF at 1 volt. By connecting 3 such artificial stone supercapacitors in series, the voltage can be increased to 2.3V. In summary, this rechargeable nano-polymer artificial stone-based supercapacitor reaches an energy density of about 13-14Wh / kg (equivalent to 0.014KWh / kg), which is the highest value achieved so far. The largest electric vehicle battery currently can store about 100kWh. With a consumption of 15 to 25kWh / 100 kilometers, electric vehicles such as Tesla Model S / X, Jaguar I-Pace or Audi e-tron can travel 400km to 600km on a single battery charge. Therefore, in order to store such a large amount of electrical energy, 7142kg of rechargeable nano-polymer artificial stone-based supercapacitors are required. Typically, a one-meter-high brick wall weighs 190kg to 440kg / m 2 , 190kg corresponds to a thickness of 100mm, and 440kg corresponds to a thickness of 230mm. Taking an exterior wall 230mm thick and 2.5m high as an example, the wall weighs 440kg per meter of length × 2.5m, or 1100kg / m. In other words, 7142kg: 1100kg / m = 6.49m. Therefore, an exterior wall 2.5m high, 230mm thick, and 6.5m long will store 100kWh of electricity!

[0065] See again Figure 2 The artificial stone supercapacitor provided by the present invention includes a matrix mortar 1, a positive electrode 2 and a negative electrode 3. The matrix mortar includes a geopolymer 11, cement 12, an alkaline activator 13, a stone additive 14, carbon black 15 and MXene 16. The matrix mortar 1 contains a preset number of free ions that can move in a direction to generate current. The positive electrode 2 and the negative electrode 3 are coated with MXene and placed in the concrete mortar, 8 mm apart from each other.

[0066] The method for preparing a complete artificial stone as a capacitor comprises the following steps:

[0067] A1) preparing an alkaline activator consisting of a potassium silicate (K2SiO3) solution containing SiO2=7.98 g, KOH=9.21 g, H2O=15 g;

[0068] A2) preparing an additive solution comprising: polycarboxylate ether = 0.25 g, retarder = 0.01 g, lignin sulfonate = 0.2 g, ethylene vinyl acetate = 0.2 g, hydroxypropyl methylcellulose = 0.1 g and pigment = 0.5 g; stirring all additives in 5 g of deionized water for 30 minutes;

[0069] A3) 1.44 g of carbon black was ultrasonically treated with a probe in 5 g of water.

[0070] A4) 0.08 g of MXene was dispersed in 5 g of water by ultrasonication for 5 minutes.

[0071] A5) Then add the entire solution to fly ash, cement, gravel and sand, i.e. 20 g fly ash, 25 g cement and 5 g gravel and sand, and mix well.

[0072] The preparation method of the steel electrode coated with MXene can be carried out by the detailed example given below, through:

[0073] B1) MXene (d-Ti3C2T x ) suspension.

[0074] B2) 0.5 g of Ti3AlC2 was slowly added into the mixture over a period of about 5 minutes, and the mixture was reacted at 35°C with stirring for 24 hours.

[0075] B3) The MXene suspension was sonicated using a probe sonicator for 1 h.

[0076] B4) The MXene suspension was then centrifuged at 3500 rpm for 30 minutes, and the supernatant was collected and used as the MXene suspension.

[0077] B5) Ag NPs (0.03 mg / mL) were added to the MXene suspension under vigorous stirring, and the solution was stirred for another 30 min.

[0078] B6) Steel was cut into dimensions of 70 mm x 60 mm x 20 mm. The resulting suspension was sprayed 7 times on a cut mesh having a polyethylene terephthalate film prebaked on a hot plate at 50°C.

[0079] C) placing the positive steel electrode 2 and the negative steel electrode 3 into a rectangular mold, and fixing the positive steel electrode 2 and the negative steel electrode 3 at a distance of 8 mm from each other,

[0080] D) Pour the prepared mortar into the mold,

[0081] E) The solution is allowed to stand to obtain a mixed solid solution.

[0082] In particular, in step E, the mixed solution is dried at ambient temperature for 24 hours and then placed in an oven at 50°C for 24 hours. In particular, the ordinary fly ash is primary fly ash and the cement is type 2 Portland cement. The alkaline activator is made of potassium hydroxide powder and silicon dioxide powder. Preferably, the alkaline activator is made of 30.7 parts of potassium hydroxide powder and 26.6 parts of silicon dioxide powder by mass. In particular, the additive is stirred in water for 30 minutes. Preferably, the carbon black is ultrasonically treated with a probe for 5 minutes. In particular, the MXene is d-Ti3C2T x . Preferably, the MXene is ultrasonically treated with a probe for 5 minutes. In particular, the steel electrode is coated with a mixture of MXene and Ag. In particular, the steel electrode comprises a positive steel electrode 2 and a negative steel electrode 3 fixed in a mortar matrix 1. The negative electrode 3 and the positive electrode 2 are fixed at a distance of 8 mm from each other.

[0083] Embodiment 1:

[0084] The artificial stone capacitor will be described in more detail and more specifically in conjunction with the examples below, but these examples are not intended to limit the present invention. The stone is made by mixing fly ash and cement into an alkaline activator (fly ash-cement) and mixing gravel and sand, i.e. 20 grams of fly ash, 25 grams of cement and 5 grams of gravel and sand. The alkaline activator consists of a potassium silicate (K2SiO3) solution, wherein SiO2=7.98 grams, KOH=9.21 grams and H2O=15 grams. Some additives are added to the stone combination, such as polycarboxylic acid=0.25 grams, retarder=0.01 grams, lignin sulfonate=0.2 grams, ethylene-vinyl acetate=0.2 grams, hydroxypropyl methylcellulose=0.1 grams and pigment=0.5 grams, carbon black=1.44 grams and MXene=0.08 grams, Ag nanoparticle solution=0.03 mg / ml. All additives are stirred in 5 grams of water for 30 minutes, and the carbon black is ultrasonically treated with a probe for 5 minutes. MXene was ultrasonically dispersed in 5 g of water for 5 min and added to cement and fly ash along with an alkali solution. All components were mixed with a mixer for 3 min. After mixing, the slurry was poured into a plastic mold to form a capacitor in the shape of a rectangular plastic brick. Two steel mesh electrodes 2 and 3 with dimensions of 70 mm × 60 mm × 20 mm were used. They were first cleaned with soap, water and acetone, then coated with a mixture of MXene and Ag and inserted into the capacitor, and the sample was vibrated to ensure good contact between the electrode and the substrate. The distance between the electrodes was 8 mm. The prepared capacitor was cured at room temperature for 24 h. It was then cured in a vacuum oven at 50 °C for 24 h.

[0085] To prepare a steel electrode coated with a MXene and Ag mixture film, 0.8 g of LiF was added to 10 ml of 9M HCl and stirred for about 5 minutes. Then 0.5 g of Ti3AlC2 was added to the mixture for about 5 minutes and reacted at 35°C and stirred for 24 hours. The MXene suspension was sonicated for 1 hour using a probe sonicator. It was then centrifuged at 3500 rpm for 30 minutes. The supernatant was collected and used as a MXene suspension. Ag NPs (0.03 mg / mL) were added to the MXene suspension under vigorous stirring, and the solution was stirred for another 30 minutes. The steel was cut into a size of 70 mm × 60 mm × 20 mm. The resulting suspension was sprayed 7 times on a cut mesh having a polyethylene terephthalate film that had been pre-baked on a hot plate at 50°C.

[0086] The rated voltage of the supercapacitor of this embodiment 1 is 1.1 volts, and its capacity is also calculated, which is 35mF. In order to increase the voltage, a series circuit operation is performed. Three capacitors are connected in series. It can be charged to 2.3V in 24 hours. In addition, the total capacity of the capacitor is calculated to be 89mF.

[0087] The above disclosed contents are only preferred embodiments of the present invention, and certainly cannot be used to limit the scope of the present invention. Therefore, equivalent changes made according to the claims of the present invention still fall within the scope of the present invention.

[0088] These artificial stones with the ability to store electrical energy offer unique opportunities, such as for the construction of buildings, thereby using buildings to provide the ability to intermediately store electrical energy and release it on demand. For example, LEDs can be powered to illuminate streets and buildings. Or 4G connectivity and higher connectivity can be powered in remote areas. The artificial stone can also be used to pair with solar panels to power sensors built into concrete structures, such as long bridges or highways.

Claims

1. Artificial stone with electric energy storage function, comprising: A geopolymer-cement matrix (1) made of a geopolymer cement-based composite material as a conductive mortar, and a positive steel electrode (2) coated with MXene and a negative electrode (3) coated with MXene immersed in the geopolymer-cement matrix (1) as an electrolyte matrix, thereby providing an electrical energy storage function.

2. The artificial stone according to claim 1, wherein: The artificial stone contains additives, and the additives are selected from one or more of polycarboxylate ethers, retarders, lignin sulfonates, ethylene vinyl acetate, hydroxypropyl methylcellulose, pigments, carbon black and MXene.

3. The artificial stone according to claim 1, wherein: The geopolymer-cement matrix (1) comprises fly ash and cement as well as gravel and sand in an alkaline activator, i.e. 20 g of fly ash, 25 g of cement and 5 g of gravel and sand; wherein the alkaline activator is composed of a potassium silicate (K2SiO3) solution, wherein SiO2=7.98 g, KOH=9.21 g, H2O=15 g; some additives are added to the stone combination, such as polycarboxylate ether=0.25 g, retarder=0.01 g, lignin sulfonate=0.2 g, ethylene vinyl acetate=0.2 g, hydroxypropyl methylcellulose=0.1 g, pigment=0.5 g, carbon black=1.44 g and MXene=0.08 g.

4. The artificial stone supercapacitor according to any one of the preceding claims, wherein: The matrix has micropores and contains a predetermined number of free ions that can move in a directed manner to generate an electric current.

5. Use of MXene according to claims 1-4 in mortar, wherein the use enhances the electrical and mechanical properties of the stone and improves the capacity and pressure resistance of the supercapacitor.

6. According to the preceding claim 1, wherein: The coating of MXene and Ag on steel electrode (2, 3) includes: LiF = 0.8 g, HCl = 10 ml, Ti3AlC2 = 0.5 g, Ag nanoparticles = 0.03 mg / ml, steel, polyethylene terephthalate film.

7. The steel electrode in the supercapacitor according to claims 1 and 6, the steel electrode having a MXene mixture layer, which shows great potential in electrochemical energy storage.

8. A method for producing an artificial stone as claimed in any one of the preceding claims, comprising the steps of: A) preparing a conductive mortar as a slurry, B) Preparation of steel electrodes coated with MXene and Ag mixture, C) Two steel electrodes are placed in the mold, D) Pour the conductive paste into the mold, E) curing the conductive slurry for 48 hours to obtain a solid artificial stone supercapacitor.

9. A method for manufacturing the artificial stone according to claim 4, comprising the following steps: A1) preparing an alkaline activator consisting of a potassium silicate (K2SiO3) solution containing SiO2=7.98 g, KOH=9.21 g, H2O=15 g; A2) preparing an additive solution, the additive solution comprising: polycarboxylate ether = 0.25 g, retarder = 0.01 g, lignin sulfonate = 0.2 g, ethylene vinyl acetate = 0.2 g, hydroxypropyl methylcellulose = 0.1 g and pigment = 0.5 g; all additives were stirred in 5 g of deionized water for 30 minutes; A3) 1.44 g of carbon black was sonicated in water using a probe; A4) adding the obtained solution to 20 g of fly ash, 25 g of cement and 5 g of gravel and sand, and then stirring evenly, and then letting stand to obtain a mixed solution; B) Preparation of steel electrodes coated with a mixture of MXene and Ag; C) placing the positive steel electrode (2) and the negative steel electrode (3) in a rectangular mold, and fixing the positive steel electrode (2) and the negative steel electrode (3) at a distance of 8 mm from each other; D) pouring the prepared mortar into a mold; E) The solution is allowed to stand to obtain a mixed solid solution.

10. A method for producing the MXene-coated steel of claims 6 and 9, comprising the steps of: B1) MXene (d-Ti3C2T x ) suspension; B2) 0.5 g of Ti3AlC2 was slowly added to the mixture over a period of about 5 minutes, and the mixture was reacted at 35° C. with stirring for 24 hours; B3) using a probe sonicator to sonicate the MXene suspension for 1 hour; B4) the MXene suspension was then centrifuged at 3500 rpm for 30 minutes; the supernatant was collected and used as the MXene suspension; B5) Ag NPs (0.03 mg / mL) were added to the MXene suspension under vigorous stirring, and the solution was stirred for another 30 min; B6) Steel was cut into dimensions of 70 mm x 60 mm x 20 mm; the resulting suspension was sprayed 7 times on the cut mesh having a polyethylene terephthalate film prebaked on a hot plate at 50°C.

11. Use of the artificial stone with electric energy storage function according to any one of claims 1 to 4 in the construction of buildings, thereby providing the ability to intermediately store electric energy and release electric energy on demand.

Citation Information

Patent Citations

  • Geopolymer-based supercapacitor power storage building and preparation method thereof

    CN113436899A

  • Geopolymer-based supercapacitor and preparation method thereof

    CN113436907A

  • Conductive slurry for preparing supercapacitor and preparation method thereof

    CN113666654A

  • Voltage source with an electrolyte containing aluminium and silicon oxides, and method for manufacturing the voltage source

    US20210119249A1

Cited By

  • Flexible aluminoferrite cement-based supercapacitor and preparation method thereof

    CN120199623A